Formation and implementation of personnel policy as a condition of effective functioning of the organization - O. V. Babich (Путеводитель предпринимателя, 2020)
The article deals with the formation, implementation and evaluation of the personnel policy of the enterprise. At present, the personnel policy of an enterprise is a conscious and purposeful activity in creating a workforce capable of combining the goals and priorities of the enterprise and its employees.